Influence of nanodispersed compositions on structure formation of high-strength aluminum alloys - Kalinina, N. E.; Hlushkova, D. B.; Voronkov, A. I.; Kalinin, A. V.; Stepanuk, A. I.; Voronova, E. M.; Serzhenko, I. O.; Калініна, Наталія Євграфівна; Калінін, Олександр Васильович; Глушкова, Діана Борисівна; Воронков, Олександр Іванович; Степанюк, Андрій Іванович; et al. (Харківський національний автомобільно-дорожній університет, 2020)
An analytical review of the state of the problem of aluminum alloys modification was performed. The absence of a unified approach to solving the problem has been established, which is asso-ciated with the complexity of the process of modifying multicomponent alloys. The aluminum alloys of the AL-Zn-Mg-Cu system were studied. As a modifier, a composition based on nanodispersed powders of titanium and boron with fractions of up to 100 nm, obtained with plasma-chemical synthesis, is proposed. The structure, phase composition, and properties of the test samples were studied before and after modification with methods of optical microscopy, X-ray diffraction analysis, and X-ray spectral analysis. In the modified B95 and B96 alloys, grain refinement and structure stabilization were achieved. Determination of the crystal lattice parameters of the alloys showed an increase in the period of lattice of the modified samples by 1.02%. The microhardness of α-Al, the solid solution, was increased from 1080 to 1500 MPa. The phase composition of B95 and B96 alloys is represented with the intermetallic phases CuAl2, MgZn3, Mg2Zn3, Mg2Si, FeAl3, TiB2, TiAl3, as well as phases of complex composition. The maximum grain refinement and increase in the mechanical properties of the alloys were achieved upon modification of 0.05% Ti and 0.005% B, which is explained by the formation of dispersed strengthening intermetallic phases of complex composition in the center of the grains.
Вплив обробки нанодисперсними композиціями на структуроутворення високоміцних алюмінієвих сплавів
Влияние обработки нанодисперсными композициями на структурообразование высоко-прочных алюминиевых сплавов
Keywords: aluminum alloys; structure; phase composition; intermetallic phases; nanomodifier; titanium; boron; алюмінієві сплави; фазовий склад; структура; інтерметалічні фази; наномодифікатор; титан; бор; алюминиевые сплавы; фазовый состав; интерметаллические фазы; наномодификатор; 620.175.2:669.15; 10.30977/BUL.2219-5548.2020.91.0.34